Gatekeeping Practices in Interpreted Social Service Encounters - Pöllabauer, Sonja (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2012)
This paper presents results gathered from a project implemented by an interdisciplinary project team between 2007 and 2009, which focused on interpreting in social service and welfare institutions (Community Interpreting und Kommunikationsqualität im Sozial- und Gesundheitswesen[Community Interpreting and Communication Quality in Social Service and Healthcare Institutions]). One of the aspects investigated by the project was the interpreting practice at two Austrian municipal social service and welfare institutions via in-depth interviews and recordings of authentic interpreter-mediated encounters. After a brief overview of the history of gatekeeping theory and the application of the gatekeeping concept in Translation and Interpreting Studies, some of the project results are analysed using one specific model of gatekeeping theory proposed by Shoemaker and Vos in 2009. Taking a leaf from this work, the analysis is based on five different levels, namely the individual level, communication routines, the organisation level, the social institutional level, and the social system level. The analysis investigates “gates” present in the communication routines at the two institutions and which may prevent non-German speaking clients from full access and understanding, as well as the role of interpreters as “gatekeepers.”